The objects in observations of Perseus cluster region. Issue 1 (28th January 2021) - Sinitsyna, Vera G.; Sinitsyna, Vera Yu.
Abstract: The results of 20‐year observations of the Perseus cluster centering on the NGC 1275 including IC 310 radio galaxy and extragalactic supernova SN 2006gy at energies 800 GeV to 45 TeV by the SHALON telescope are presented. Also, the emission from the galactic source of non‐thermal radio and X‐ray emission GK Per (Nova 1901) of classical nova type was found as it accompanied to the observations. For NGC 1275, it was found that the TeV γ ‐ray emission at energies >800 GeV has an extended structure with a distinct core centered at the NGC 1275 nucleus and well correlates with the photon emission regions viewed in X‐rays by Chandra and anti‐correlates with radio‐structures. Also, the variations of TeV γ ‐ray flux both at year‐ and day scales were found. The obtained data indicate that the part of TeV γ ‐ray emission is generated by relativistic jets in the nucleus of NGC 1275. Whereas the presence of an extended structure around NGC 1275 and the slow rise of the γ ‐ray flux is the evidence of the interaction of cosmic rays and magnetic fields generated in the jets at the galactic center with the gas of the Perseus cluster.